CHARACTERISTIC AND EFFECTS OF A SUPERPLASTICIZER QUANTITY VARIATION IN SOME CONCRETE STRENGTHS OPTIMIZATION (Nigerian Journal of Technology, 2018)
This study investigates the properties of superplasticized concrete and compared results to that of normal concrete. Four different concrete proportioning of 1:2:3 mix ratio have been considered. A0 is normal concrete having 0.4 water cement ratio (w/c) and is the control while A1, A2 and A3 are superplasticized concretes having 0.3 water cementitious materials ratio (w/cm) with varied percentages of the superplasticizer.  Beams, cubes and cylinders, 60 each were cast, de-moulded and cured. They were tested for strengths at different days of curing; 7, 28, 56, 90 and 120 days. Appropriate casting of fresh concrete paved way for 60 beams, 60 cubes and 60 cylinders specimens which were subjected to 7, 28, 56, 90 and 120 moist cured days and were duly subjected to strength tests. Tests on the material constituents used for the concrete production showed that they satisfied standard specification requirements. The workability test results on fresh concretes showed that as the dosage of superplasticizer is increasing the values of both slumps and compaction factors are increasing. Significantly, the flexural, compressive and tensile splitting tests results showed that as workability of the fresh concrete is increasing the related hardened concrete strength is also increasing. An improvement in the appearance (smoothness) was observed in the specimens produced as the superplasticizer dosage increases.  Keywords: Experimental, Properties, Proportioning, Superplasticizer, Concrete  http://dx.doi.org/10.4314/njt.v38i1.11